Development of Wordwall Media Based on Problem Based Learning in IPAS Learning for Fourth Grade Elementary School - Juni Faivantisa Wisda; Yeni Erita; Leni Zahara; Rayendra Rayendra (FKIP - Universitas Riau, 2026)
This research aims to develop learning media using Wordwall based on Problem Based Learning (PBL) in the subject of Natural and Social Sciences (IPAS) for fourth grade elementary school students. The research method employed was Research and Development (R&D) using the ADDIE model, which includes analysis, design, development, implementation, and evaluation. The participants of this research were students from several elementary schools in Lubuk Begalung, Padang City. Data were collected through expert validation sheets, practicality questionnaires, and student achievement tests. The validation results by media, material, and language experts indicated that the developed media was highly valid. The practicality test showed that both teachers and students found the media easy to use, engaging, and beneficial. Furthermore, the effectiveness test using pre-test and post-test demonstrated significant improvement in student learning outcomes with an average N-Gain score of 0.72, categorized as high. Therefore, Wordwall media integrated with PBL can serve as an innovative solution to improve the quality of IPAS learning in elementary schools.